The study of religion as passionate engagement: The visionary sensibility of talal asad - Auwais Rafudeen (Journal for the Study of Religion)
As interpreted by this essay, Asad locates the key features of the secular perspective as residing in representation, quantification and the autonomy of the individual. These features are inscribed in the way the secular, and a religious studies implicated by this secular, approaches religion. But in analyzing these features, Asad uncovers alternate ways of approaching religion, ways that do not categorize religion within a broader secular project, but engage its manifestations as sense-driven, passionate, transforming forms of life. These ways, we believe, have implications for the notions of 'theory' and 'method' in religious studies.